Risk assessment for industry - Vocam Worldwide Publishing ([Victoria, Australia] : Vocam Worldwide Publishing, 1999)
This interactive training program is designed to help with the implementation of a thorough risk assessment strategy with an eye on making all staff feel a part of the this very important process
Title from title screen
VCD format
Keywords: Industrial safety; Risk assessment; Explosion prevention and protection